De invloed van Brussel op het Frans in België - Michel Francard (Brussels Studies)
The role of big cities in the evolution of languages has held the attention of linguists for decades. As places of constant coming and going, mixing and exchanging, urban centres are real hubs for linguistic innovation, with an impact which extends far beyond the city limits. The influence of major urban centres on the evolution of French in Belgium has not yet been studied in detail as regards the present or the past. This article is in keeping with this theme, with an examination of the French spoken today in Brussels. Following a short review of the history of the languages spoken in the capital and a clarification of the sometimes misleading label “Brussels French”, this study discusses the Germanic component of the “Brussels” vocabulary, by distinguishing between the forms and idioms specific to the capital and those which are shared with Wallonia. Through these examples, we shall attempt to better understand the status of the French spoken in Brussels and the role of the capital in the dynamics of the French used in Belgium.